E-health – The importance of the internet as an informative digital health application for gynecological patients in times of SARs-CoV2: A national cross-sectional survey. (2022) - Hertling, Stefan; Hertling, Doreen; Schleußner, Ekkehard; Loos, Franziska; Graul, Isabel
Abstract: Introduction: The internet plays an important role as a digital source of information. The aim of this work is to investigate patients with disorder of the female sex organ (malignant and benign) to examine their information behavior about their diseases. The role and importance of the internet as an informative health application for these patients in this context will be highlighted. Materials and methods: This prospective cross-sectional study was based on a survey of patients in Germany during the Coronavirus disease (COVID-19) pandemic among gynecological patients from July 2020 to November 2021. Descriptive statistics were calculated, and simple linear regression analysis was performed to show correlations. Results: We analyzed the responses from 1271 gynecological patients. 91.4% (n = 1162) had an internet-enabled device. Of these, over 55% (n = 644) go online with a smartphone. Only eight percent (n = 101) stated to never feel able to use internet-enabled devices. In addition, almost 47% (n = 596) say that their attitude towards internet-enabled devices changed due the COVID-19 pandemic in a positive way. 82% (n = 1042) of patients can use digital health applications. In addition, more than 82% (n = 1046) believe that the use of digital health applications can have a positive impact on their disease treatment. Due to the COVID-19 pandemic, the attitude towards digital health applications changed positively in 41.4% (n = 526). More than 73% of patients (n = 933) reported using DHAs more frequently. 76% of patients (n = 966) use the internet as a source of information about their gynecological health problem. Over 90% of them (n = 874) regularly use the internet for this purpose. Over 73% of patients (n = 928) state that the internet has become an important source of health information for them since the COVID-19 pandemic. For gynecological problems, two thirds of them (621/928) use the internet as a source of health information before consulting a physician. Conclusion: The internet as an informative digital health application in gynecology is used extensively and is widely accepted by patients. Mistrust of gynecological health information from the internet has diminished because of the COVID-19 pandemic. Confidence in informative digital health applications from the patient's point of view has increased. The internet was seen as a helpful health information platform in addition to medical consultation. More specialized research in the field of e-health in gynecology is needed. This includes large-scale randomized controlled trials, economic analysis, and explorations of user preferences to increase the confidence and usefulness of informative digital health applications in the future. The most reported benefit of the internet as a digital informative health application was time-independent use. The main obstacles were a lack of trust and evidence of the lack of health information from the internet. Highlights: Patients have a positive attitude towards E-health. The Internet as an informative digital health application in gynecology is used extensively and is widely accepted by patients. Confidence in informative digital health applications from the patient's point of view has increased. Mistrust of gynecological health information from the Internet has diminished because of the corona pandemic. The Internet plays an increasingly important role in patients' search for health care information.